Ask Question
1 April, 14:27

F (x) = 2x - 1 g (x) = 7x - 12 What is h (x) = f (x) + g (x) ?

+1
Answers (1)
  1. 1 April, 14:45
    0
    h (x) = 9x - 13

    This is because when you add 2x and 7x you get 9 x and - 1 - 12 equals - 13 making 9x - 13.
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “F (x) = 2x - 1 g (x) = 7x - 12 What is h (x) = f (x) + g (x) ? ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers